What robots want? Hearing the inner voice of a robot - Pipitone, Arianna (iScience, 2021)
The inner speech is thoroughly studied in humans, and it represents an interdisciplinary research issue involving psychology, neuroscience, and pedagogy. A few papers only, mostly theoretical, analyze the role of inner speech in robots. The present study investigates the potential of the robot's inner speech while cooperating with human partners. A cognitive architecture is designed and integrated with standard robot routines into a complex framework. Two threads of interaction are discussed by setting the robot operations with and without inner speech. Thanks to the robotic self-dialog, the partner can easily trace the robot's processes. Moreover, the robot can better solve conflicts leading to successful goal achievements. The results show that functional and transparency requirements, according to the international standards ISO/TS:2016 and COMEST/Unesco for collaborative robots, are better met when inner speech accompanies human-robot interaction. The inner speech could be applied in many robotics contexts, such as learning, regulation, and attention.